EDTA-enhanced electrokinetic remediation of aged electroplating contaminated soil assisted by combining dual cation-exchange membranes and circulation methods. (March 2020) - Song, Yue; Cang, Long; Zuo, Yilin; Yang, Jiangli; Zhou, Dongmei; Duan, Tigang; Wang, Renqing
Abstract: This paper introduces a novel method for ethylenediaminetetraacetic acid (EDTA)-enhanced electrokinetic (EK) remediation by combining dual cation-exchange membranes and circulation methods for an aged electroplating soil contaminated by chrome (Cr), copper (Cu), and nickel (Ni). Three laboratory-scale EK experiments were carried out, including T1, the traditional EK process; T2, the traditional EDTA-enhanced EK process; and T3, the assisted EDTA-enhanced EK process. The results obtained show that removal of Cu and Ni in T3 was 3–10 times higher than after T1 and T2. However, the removal of Cr (total) was small in all experiments because of the high content of Cr(III). T3 eliminated the metal accumulation problem that existed for T1 and T2. Simultaneously, the highly acidified area (pH < 4) was reduced from 80% in T1 and T2 to only 20% in T3. The results obtained in T3 indicate that the chelating effect of EDTA has a greater ability to dissolve oxidizable Cu and Ni in the soil than the acidification effect. Toxicity evaluation confirmed that the soil treated by T3 presented a lower effect on a luminescent bacterium ( Photobacterium phosphoreum T3 ) because soil pH tended to be more neutral after this treatment. This research provides a novel method for removing heavy metals from soil in a more environmentally friendly way and clarifies the cause of the existing problems of low removal efficiency and high accumulation in the traditional EK process. Graphical abstract: Image 1 Highlights: DCEK and CEEK assist EDTA-enhanced EK for treating various metals. More Cu and Ni removals compared to traditional EK strategies. Low metal accumulation and smaller acidified area realized. Soil treated by dual CEMs and circulation assisted EDTA-enhanced EK was less toxic.